(untitled) (Chittagong University Journal of Biological Sciences, 2013)
The macro- and micro-nutrients of locally produced pineapples namely Giant Kew and Honey Queen were compared. The Giant Kew variety contained 6 g% of TSS, 3.88 g% of total sugar and 1.75 g% of non reducing sugar. On the contrary, the Honey Queen variety contained 10 g% of TSS, 4.84 g% of total sugar and 1.59 g% of non reducing sugar. The comparative study indicates that the Honey Queen variety is superior in nutritional content as well as sweetness than the Giant Kew variety of pineapple. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13375 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):105-112, 2010